Correction: Methods for Developing Evidence Reviews in Short Periods of Time: A Scoping Review. - Ahmed M Abou-Setta; Maya M Jeyaraman; Abdelhamid Attia; Hesham G Al-Inany; Mauricio Ferri; Mohammed T Ansari; Chantelle M Garritty; Kenneth Bond; Susan L Norris (PLoS ONE, 2017)
[This corrects the article DOI: 10.1371/journal.pone.0165903.].